IMPLEMENTASI APLIKASI SABILULUNGAN SISTEM PENILAIAN KINERJA PEGAWAI (SASIKAP) - B, Asri; Tiarani, Sheila Novelia (Jurnal Teknologi dan Komunikasi Pemerintahan, 2021)
The Sabilulungan Employee Performance Assessment System (SASIKAP) launched by the Bandung Regency Government is an innovation that is used as a reference for electronic-based PNS performance assessments in an effort to give rewords and penalties. Reference to Regent Regulation No. 18/2019 regarding Employee Performance Assessment has brought many changes to the way of working, including the implementation of good governance principles due to strong control from stakeholders. The method used in this research is qualitative with a descriptive approach. Collecting data in the form of interviews, observations and reviewing documents related to the research. The determination of informants was based on certain qualifications, including the authorities because they were considered the most knowledgeable about the object being studied related to the SASIKAP. The informants in this study were 9 BKPSDM employees with different levels of position. The results of the study found that based on Edward III's Theory, namely Communication, Resources, Disposition and Bureaucratic Structure, it had been implemented quite well, but from the indicators contained in the communication and resource dimensions there were still obstacles because employees had not fully mastered the use of digital technology related to the procedure for filling out results. The work on the SASIKAP application was caused by a lack of socialization from related parties, only one SASIKAP admin employee, and as a result were overwhelmed in providing services to all employees at the Bandung Regency BKPSDM. Keywords : Implementation, Employee, Performance Appraisal, Sabilulungan, SASIKAP